Effect of memory and reinforcement on the fatigue failure of elastic materials - Esleta, George Allan P.; Monterola, Christopher P. (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2009)
We investigate the interplay of two opposing mechanisms, namely damage accumulation and structural reinforcement, in the fatigue failure of a two-dimensional mass-spring system. The buildup of damage is captured in the model by introducing memory to the spring elements, such that the accumulated damage of a spring at a certain time depends on its deformation history. Structural reinforcement, on the other hand, is implemented by increasing the breaking thresholds of the springs.
Thesis (Master of Science in Physics)--University of the Philippines Diliman
Keywords: Elastic rods and wires